Exploring Experience: A Case for Phenomenology in Pentecostal Studies - Åkerlund, Truls (Pneuma, 2023)
This article contributes to pentecostal research by arguing that applied phenomenology can enhance the understanding of pentecostal experience and enrich work with systematic theology by increasing the amount of relevant data. Phenomenology is especially appropriate for pentecostal theology and research due to the shared emphasis on embodiment, importance of experiences, consistency of appearances, and realism of phenomena. Despite this methodological fit, our systematic literature review reveals a lack of phenomenological works in the corpus of pentecostal studies, and we provide some considerations for integration and suggestions for further empirical research grounded in a phenomenological sensibility.